A Review of Cold Atmospheric Pressure Plasmas for Trauma and Acute Care - Garner, Allen L.; Mehlhorn, Thomas A. (Frontiers in Physics, 2021)
Despite the high overall survival rates of severely injured military and civilian personnel requiring trauma and acute care, the challenges of treating infections and healing-resistant wounds have grown. Exposure to unknown environmental pathogens at the wound, including parasites and antibiotic resistant microorganisms, hinders timely and effective treatment using traditional techniques. Cold atmospheric pressure plasma (CAPP) provides a promising biophysical tool to address these issues by applying physically created modalities that cannot be circumvented by bioresistance to inactivate microorganisms and enhance wound healing. CAPPs generate charged particles and numerous reactive oxygen species (ROS) and reactive nitrogen species (RNS) that act on biological cells and tissues, often through plasma membrane interactions. This review fills a gap in the plasma medicine literature by specifically focusing on applying CAPPs for acute trauma, such as surgery, wound treatment, and disinfection. After briefly highlighting the areas of opportunity for improving acute trauma treatment and the fundamentals of CAPP generation, this review details emerging applications of CAPPs for enhanced wound healing, burn treatment, transdermal delivery, and surgical applications. We also discuss CAPP optimization through novel device design and synergistic combination with traditional treatment technologies to transition this biophysical technology to the battlefield and acute care settings.